The Nasal Locator: An Innovative Instrument to Define the Exact Point of Osteotomy in Preservation or Structural Rhinoplasty - Mireas, George (Facial Plastic Surgery, 2024)
One of the most common components of most dorsal preservation (DP) techniques is subdorsal septal excision. Whatever the instrument used for this procedure (piezoelectric, Rongeur, or long scissors), it is paramount to be able to determine the exact subdorsal point (SDoP) at which the osteotomy/ostectomy (or cartilage cut) has been reached. First, to avoid any unnecessary extension of the osteotomy that increases the risk of fracture spreading into the cribriform plate and a consequent cerebrospinal fluid leak; second, to be sure that the subdorsal cut is high enough and can be combined/unified with the planned radix osteotomy.In addition, transverse osteotomies are usually necessary in both preservation and structural rhinoplasties. Even though many surgeons are satisfied with their osteotomy lines, it sometimes proves difficult to be sure of their position, especially during a DP rhinoplasty when both the transverse lines have to go in the direction of the planned radix osteotomy.We have developed the Nasal Locator (NL) to precisely define various nasal points of interest, such as a subdorsal cut (cartilaginous or bony), or a transverse or medial osteotomy line. It ends in two tips. The lower tip is placed at the point we wish to determine (e.g., SDoP or a transverse osteotomy), while the upper tip is fixed a certain distance from it (in all three dimensions), showing its exact location.Our in-depth research of the literature and the market has not revealed any device similar in form and function to the NL.We have been using the NL for almost 2 years and are confident of its usefulness. It is easy to use, and practically no time is needed to become familiar with it. During surgery, it is needed for less than 30 seconds and is risk-free. It is fully sterilizable and can be used repeatedly.
Keywords: nasal locator; subdorsal point; dorsal preservation; preservation rhinoplasty; structural rhinoplasty; instrument